Conductive slurry and preparation method thereof, electrode and battery

By introducing onium compounds as calcination promoters into the conductive paste of heterojunction solar cells, the conductivity of the silver-clad copper electrode and the contact performance of the electrode with the TCO substrate are improved, and the problems of high cost and low efficiency of the low-temperature silver paste are solved, and the cost reduction and efficiency increase effect is achieved.

CN119626625APending Publication Date: 2025-03-14LUCKY FILM CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411830168.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

In heterojunction solar cells, the high usage and low conductivity of low-temperature silver paste lead to high production costs and low efficiency, making it difficult to achieve synchronous optimization of cost reduction and efficiency improvement.

Method used

By introducing the calcination-enhancing agent onium compound into the conductive paste, the conductivity of the silver-clad copper electrode is improved and the contact resistance between the electrode and the TCO substrate is reduced. Conductive powders such as silver powder and silver-clad copper powder are used to combine thermally curable components and curing agents to prepare a slurry with excellent conductivity.

Benefits of technology

It has achieved the reduction of silver usage and production costs, while improving the photoelectric conversion efficiency of the battery, achieving the optimization effect of reducing costs and increasing efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_12
    Figure SMS_12
  • Figure SMS_13
    Figure SMS_13
Patent Text Reader

Abstract

The invention discloses conductive paste and a preparation method thereof, an electrode and a battery. The conductive paste includes a conductive powder, a thermosetting component, a curing agent, a firing accelerator, and a solvent, the firing accelerator including an onium compound, and the conductive powder including at least one of silver powder and silver-coated copper powder. Therefore, by adding the burning promoter onium compound into the conductive slurry, the conductivity of the electrode can be improved, the contact resistance between the electrode and the TCO substrate (transparent conductive film) is reduced, the resistance loss of the electrode is reduced, the photoelectric conversion efficiency of the battery is improved, and cost reduction and efficiency improvement can be realized at the same time.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of battery technology, and in particular to a conductive paste and a preparation method thereof, an electrode and a battery. Background Art

[0002] HJT cells, also called HIT cells, commonly known as heterojunction cells, are third-generation cells, and their full name is crystalline silicon heterojunction solar cells. They are silicon solar cells that use a HIT structure. This technology deposits amorphous silicon thin films on crystalline silicon, combining the core competitiveness of crystalline silicon cells and thin-film cells, and can improve the photoelectric conversion efficiency. It is one of the hot trends in high-conversion-efficiency silicon-based solar cells.

[0003] The development of heterojunction batteries is inseparable from the continuous pursuit of cost reduction and efficiency improvement. In the total cost of heterojunction batteries, the metallization cost accounts for a relatively high proportion. Due to its double-sided structure, low-temperature silver paste is required. The total amount of paste is higher than other crystalline silicon batteries. In addition, the conductivity of low-temperature silver paste is not as good as that of high-temperature paste. Therefore, it is necessary to increase the line width or number of lines to meet the high electrical requirements of the electrode, further increasing the paste cost.

[0004] Therefore, for low-temperature slurry, if the efficiency improvement and cost reduction of heterojunction batteries can be achieved simultaneously, it will play an important role in promoting the development of heterojunction batteries. Summary of the invention

[0005] The present application aims to solve at least one of the technical problems in the related art to a certain extent. To this end, one purpose of the present application is to propose a conductive paste and a preparation method thereof, an electrode and a battery. The conductive paste of the present application effectively reduces the production cost by reducing the amount of silver used. At the same time, the paste has excellent conductive properties after curing into a film, and its conductivity is not much different from that of pure silver paste with a silver content of more than 92wt%. This not only meets the demand for cost reduction, but also achieves the dual goal of improving the performance of heterojunction solar cells, achieving the optimization effect of reducing costs and increasing efficiency.

[0006] Therefore, in the first aspect of the present application, the present application proposes a conductive paste. According to an embodiment of the present application, the conductive paste comprises: a conductive powder, a thermosetting component, a curing agent, a sintering agent and a solvent, wherein the sintering agent comprises an onium compound, and the conductive powder comprises at least one of silver powder and silver-coated copper powder. After a large number of experiments, the inventors found that adding a sintering agent onium compound to the conductive paste can improve the conductivity of the electrode, while reducing the contact resistance between the electrode and the TCO substrate (transparent conductive film glass), as well as reducing the electrode resistance loss, and improving the photoelectric conversion efficiency of the battery.

[0007] According to an embodiment of the present application, based on the total mass of the conductive paste, the mass proportion of the sintering promoter is 0.05%-0.2%.

[0008] According to an embodiment of the present application, based on the total mass of the conductive paste, the mass proportion of the conductive powder is 88%-95%.

[0009] According to an embodiment of the present application, based on the total mass of the conductive paste, the mass proportion of the thermosetting component is 1%-10%.

[0010] According to an embodiment of the present application, based on the total mass of the conductive paste, the mass proportion of the curing agent is 0.2%-1.5%.

[0011] According to an embodiment of the present application, the onium compound includes at least one of imidazolium, sulfonium, iodonium, and ammonium.

[0012] According to an embodiment of the present application, the thermosetting component includes at least one of an epoxy resin with a polyolefin main chain, a bisphenol epoxy resin, and an alicyclic epoxy resin.

[0013] According to an embodiment of the present application, the curing agent includes at least one of a thermal cationic curing agent and a blocked polyisocyanate curing agent.

[0014] According to an embodiment of the present application, the conductive powder includes the silver powder and the silver-coated copper powder, and the mass ratio of the silver powder to the silver-coated copper powder is (20:80)-(30:70).

[0015] According to an embodiment of the present application, the thermosetting component includes the epoxy resin with the polyolefin main chain, the bisphenol epoxy resin and the alicyclic epoxy resin, and the mass ratio of the epoxy resin with the polyolefin main chain, the bisphenol epoxy resin and the alicyclic epoxy resin is (20-60):(56-20):(40-12).

[0016] According to an embodiment of the present application, the curing agent includes the thermal cationic curing agent and the blocked polyisocyanate curing agent, and the mass ratio of the thermal cationic curing agent to the blocked polyisocyanate curing agent is (0.5-1):1.

[0017] According to an embodiment of the present application, the blocked polyisocyanate curing agent is a compound formed by blocking a polyisocyanate compound.

[0018] According to an embodiment of the present application, the epoxy resin with a polyolefin main chain includes at least one of a plant polyphenol epoxy resin, an epoxidized polyolefin polyol, and an epoxidized hydroxyl acrylic resin.

[0019] According to an embodiment of the present application, the bisphenol epoxy resin includes at least one of bisphenol F epoxy resin, bisphenol S epoxy resin, and bisphenol A epoxy resin.

[0020] According to an embodiment of the present application, the alicyclic epoxy resin includes at least one of 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexylcarboxylate, bis(7-oxabicyclo[4.1.0]3-heptylmethyl)adipate, tetrahydrophthalic acid diglycidyl ester, and hexahydrophthalic acid diglycidyl ester.

[0021] According to an embodiment of the present application, the thermal cationic curing agent includes at least one of a thermal cationic curing agent containing nitrogen atoms and a thermal cationic curing agent containing fluorine atoms.

[0022] According to an embodiment of the present application, the thermal cationic curing agent includes at least one of boron trifluoride ethyl ether, boron trifluoride phenol, boron trifluoride piperidine, boron trifluoride acetate, boron trifluoride monomethylamine, boron trifluoride monoethylamine, boron trifluoride triethanolamine, and boron trifluoride monoethanolamine.

[0023] According to an embodiment of the present application, the polyisocyanate curing agent includes at least one of aromatic isocyanate and aliphatic polyisocyanate.

[0024] According to an embodiment of the present application, the aromatic isocyanate includes at least one of toluene diisocyanate, diphenylmethane diisocyanate, polymethylene polyphenyl polyisocyanate, dimethyl diphenyl diisocyanate, xylylene diisocyanate, and naphthalene diisocyanate.

[0025] According to an embodiment of the present application, the aliphatic polyisocyanate includes at least one of hexamethylene diisocyanate, isophorone diisocyanate, hydrogenated xylylene diisocyanate, dicyclohexylmethane diisocyanate, octamethylene diisocyanate, and trimethylhexamethylene diisocyanate.

[0026] In the second aspect of the present application, the present application proposes a method for preparing the conductive paste described in the first aspect. According to an embodiment of the present application, the method comprises: mixing a conductive powder, a thermosetting component, a curing agent, a sintering agent and a solvent; grinding the mixed product to obtain the conductive paste; wherein the sintering agent comprises an onium compound, and the conductive powder comprises at least one of silver powder and silver-coated copper powder. By adopting the method described in the present application, a cost-effective conductive paste can be prepared, which can not only reduce production costs, but also exhibit excellent conductive properties when used as an electrode material. In addition, the conductive paste can also effectively reduce the contact resistance between the electrode and the TCO substrate, thereby improving the photoelectric conversion efficiency of the battery. Those skilled in the art can understand that this method has all the characteristics and advantages of the conductive paste described above, and will not be repeated here.

[0027] In the third aspect of the present application, the present application proposes an electrode. According to an embodiment of the present application, the electrode is formed by curing the conductive paste prepared by the conductive paste described in the first aspect or the method described in the second aspect. Therefore, the electrode prepared by the conductive paste of the present application has good conductivity and can reduce the contact resistance between the electrode and the TCO substrate. It can be understood by those skilled in the art that the electrode has all the characteristics and advantages of the conductive paste described above, and no further elaboration is given here.

[0028] In the fourth aspect of the present application, the present application proposes a battery. According to an embodiment of the present application, the battery comprises a TCO substrate and the electrode described in the third aspect. Thus, the battery prepared using the electrode of the present application has excellent photoelectric conversion efficiency. It can be understood by those skilled in the art that the battery has all the features and advantages of the conductive paste described above, and no further elaboration is given here.

[0029] According to an embodiment of the present application, the TCO substrate includes indium tin oxide (ITO), fluorine-doped tin oxide (FTO), or tungsten-doped tin oxide (IWO).

[0030] Additional aspects and advantages of the present application will be given in part in the description below, and in part will become apparent from the description below, or will be learned through the practice of the present application. DETAILED DESCRIPTION

[0031] The embodiments of the present application are described in detail below, which are intended to be used to explain the present application but should not be construed as limiting the present application.

[0032] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.

[0033] For simplicity, only some numerical ranges are specifically disclosed herein. However, any lower limit can be combined with any upper limit to form an unspecified range; and any lower limit can be combined with other lower limits to form an unspecified range, and any upper limit can be combined with any other upper limit to form an unspecified range. In addition, each separately disclosed point or single value can itself be combined as a lower limit or upper limit with any other point or single value or with other lower limits or upper limits to form an unspecified range.

[0034] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" in the description and claims of this application and any variations thereof are intended to cover non-exclusive inclusions.

[0035] In this document, the terms "include" or "comprising" are open expressions, that is, including the contents specified in the present application but not excluding other contents.

[0036] It should be noted that the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. Further, in the description of this application, unless otherwise specified, the meaning of "plurality" is two or more.

[0037] In addition, it should be noted that, unless explicitly stated otherwise, the description methods used in this application, "each... is independently selected from" and "... are each independently selected from" and "... are independently selected from" can be interchanged, and should be understood in a broad sense, which can mean that in different groups, the specific options expressed by the same symbols do not affect each other, or that in the same group, the specific options expressed by the same symbols do not affect each other.

[0038] In general, the term "substituted" means that one or more hydrogen atoms in a given structure are replaced by a specified substituent. Unless otherwise indicated, a substituted group may have a substituent at each substitutable position of the group. When more than one position in a given structure can be substituted by one or more substituents selected from a specified group, then the substituents may be the same or different at each substitutable position.

[0039] The term "unsubstituted" means that the designated group bears no substituents.

[0040] It should be understood that the term "optionally substituted" is used interchangeably with the term "substituted or unsubstituted". In general, the term "optionally", whether or not preceded by the term "substituted", indicates that one or more hydrogen atoms in a given structure are replaced with a specified substituent. Unless otherwise indicated, an optionally substituted group may have a substituent substituted at each substitutable position of the group. When more than one position in a given structure can be substituted with one or more substituents selected from a specified group, the substituents may be substituted the same or differently at each position. The substituents mentioned herein can be, but are not limited to, deuterium, hydroxyl, amino, halogen, cyano, aryl, heteroaryl, alkoxy, alkylamino, alkylthio, alkyl, alkenyl, alkynyl, heterocyclic, thiol, nitro, aryloxy, heteroaryloxy, oxo (=O), carboxyl, hydroxy-substituted alkoxy, hydroxy-substituted alkyl-C (=O)-, alkyl-C (=O)-, alkyl-S (=O)-, alkyl-S (=O)2-, hydroxy-substituted alkyl-S (=O)-, hydroxy-substituted alkyl-S (=O)2-, carboxyl-substituted alkoxy, and the like.

[0041] In various parts of this specification, the substituents of the compounds disclosed in this application are disclosed according to group types or ranges. It is particularly pointed out that this application includes every independent subcombination of the individual members of these group types and ranges. For example, the term "C 1-6 "Alkyl" specifically refers to methyl, ethyl, C3 alkyl, C4 alkyl, C5 alkyl and C6 alkyl as disclosed independently.

[0042] The term "alkyl" refers to a saturated linear or branched monovalent hydrocarbon group of 1-10 carbon atoms, or 1-8 carbon atoms, or 1-6 carbon atoms, or 1-5 carbon atoms, or 1-3 carbon atoms, wherein the alkyl group may be independently and optionally substituted with one or more substituents described herein, including but not limited to deuterium, amino, hydroxyl, cyano, F, Cl, Br, I, mercapto, nitro, oxo (=O), etc. Examples of alkyl groups include, but are not limited to, methyl (Me, -CH3), ethyl (Et, -CH2CH3), n-propyl (n-Pr, -CH2CH2CH3), isopropyl (i-Pr, -CH(CH3)2), n-butyl (n-Bu, -CH2CH2CH2CH3), isobutyl (i-Bu, -CH2CH(CH3)2), sec-butyl (s-Bu, -CH(CH3)CH2CH3), tert-butyl (t-Bu, -CH(CH3)CH2CH3), -C(CH3)3), n-pentyl (-CH2CH2CH2CH2CH3), 2-pentyl (-CH(CH3)CH2CH2CH3), 3-pentyl (-CH(CH2CH3)2), 2-methyl-2-butyl (-C(CH3)2CH2CH3), 3-methyl-2-butyl (-CH(CH3)CH(CH3)2), 3-methyl-1-butyl (-CH2CH2CH(CH3)2), 2-methyl-1- Butyl (-CH2CH(CH3)CH2CH3), n-hexyl (-CH2CH2CH2CH2CH2CH3), 2-hexyl (-CH(CH3)CH2CH2CH2CH3), 3-hexyl (-CH(CH2CH3)(CH2CH2CH3)), 2-methyl-2-pentyl (-C(CH3)2CH2CH2CH3), 3-methyl-2-pentyl (-CH(CH3)CH(CH3)CH2CH3 ), 4-methyl-2-pentyl (-CH(CH3)CH2CH(CH3)2), 3-methyl-3-pentyl (-C(CH3)(CH2CH3)2), 2-methyl-3-pentyl (-CH(CH2CH3)CH(CH3)2), 2,3-dimethyl-2-butyl (-C(CH3)2CH(CH3)2), 3,3-dimethyl-2-butyl (-CH(CH3)C(CH3)3), n-heptyl, n-octyl, and the like. The term "alkyl" and its prefix "alkane" as used herein include both straight and branched saturated carbon chains. The term "alkylene" as used herein refers to a saturated divalent hydrocarbon radical derived from a straight or branched saturated hydrocarbon by eliminating two hydrogen atoms, such examples include, but are not limited to, methylene, ethylene, isopropylidene, and the like.

[0043] The term "alkenyl" refers to a straight or branched chain monovalent hydrocarbon radical having at least one carbon-carbon sp 2Double bonds, including "cis" and "trans" orientations, or "E" and "Z" orientations. Wherein, the alkenyl group may be optionally substituted with one or more substituents described herein. In one embodiment, the alkenyl group contains 2-10 carbon atoms; in another embodiment, the alkenyl group contains 3-10 carbon atoms; in another embodiment, the alkenyl group contains 2-6 carbon atoms; in yet another embodiment, the alkenyl group contains 2-4 carbon atoms. Examples of alkenyl groups include, but are not limited to, vinyl (-CH=CH2), allyl (-CH2CH=CH2), and the like.

[0044] The term "halogen" refers to fluorine (F), chlorine (Cl), bromine (Br) or iodine (I).

[0045] The term "aromatic" refers to a monocyclic, bicyclic or tricyclic carbon ring system containing 6-14 ring atoms, or 6-12 ring atoms, or 6-10 ring atoms, wherein at least one ring is aromatic and has one or more attachment points to the rest of the molecule. The term "aromatic" can be used interchangeably with the term "aromatic ring". In one embodiment, the aromatic group is a carbon ring system consisting of 6-10 ring atoms and containing at least one aromatic ring. Examples of aromatic groups can include phenyl, naphthyl and anthracenyl. Wherein, the aromatic group can be independently optionally substituted with one or more substituents described in the present application.

[0046] Silicon heterojunction solar cells are based on crystalline silicon. After cleaning and texturing, an intrinsic amorphous silicon layer and an N-type amorphous silicon layer are deposited in sequence on the first light-receiving surface of the front side of the crystalline silicon, an intrinsic amorphous silicon layer and a P-type amorphous silicon layer are deposited in sequence on the second light-receiving surface of the back side, and a transparent conductive oxide (Transparent Conductive Oxide: TCO) is deposited on both the first light-receiving surface and the second light-receiving surface. Finally, metal electrodes are prepared on the first light-receiving surface and the second light-receiving surface using screen printing technology and thermosetting low-temperature resin slurry to obtain silicon heterojunction solar cells.

[0047] In the study of the total cost of battery preparation, the inventors found that the metallization cost accounted for a high proportion. It is crucial to achieve the simultaneous optimization of low-temperature slurries in improving efficiency and reducing costs to promote the development of heterojunction battery technology. For metallization efficiency improvement, the conductivity of the surface electrode of the heterojunction battery is a key factor, which is further subdivided into the contact resistance between the electrode and the TCO substrate and the electrode body resistivity. The simultaneous reduction of contact resistance and volume resistivity can help increase the battery efficiency by 0.3-0.5 percentage points. For metallization cost reduction, heterojunction batteries can achieve the conversion from pure silver paste to silver-coated copper paste due to their low-temperature process advantages. At present, silver-coated copper paste with a silver content of 50wt% has completed outdoor empirical testing and is widely adopted by mainstream heterojunction battery manufacturers. In addition, silver-coated copper paste with a silver content of 20wt%-40wt% is also in the verification stage, which will further reduce material costs. However, the reduction in silver powder content may have an adverse effect on conductivity.

[0048] In view of this, the inventors, based on the starting point of cost reduction and efficiency improvement, have carried out relevant work on improving the conductivity of silver-coated copper slurry containing 20wt%-40wt% silver at low cost. The research found that by introducing organic carrier sintering promotion and conductivity enhancement technology into the slurry, the conductivity of the silver-coated copper electrode can be greatly improved. The volume resistivity and the contact resistance between the electrode and the TCO substrate are reduced simultaneously, and the effect is the same as that of pure silver slurry. The conductive slurry, its preparation method, electrode and battery will be introduced in detail below.

[0049] Conductive paste

[0050] The present application proposes a conductive paste. According to an embodiment of the present application, the conductive paste includes: a conductive powder, a thermosetting component, a curing agent, a sintering agent and a solvent, wherein the sintering agent includes an onium compound, and the conductive powder includes at least one of silver powder and silver-coated copper powder. Therefore, by introducing the sintering agent-onium compound into the conductive paste, the onium compound can produce material exchange with the surface of the silver powder, promote the mutual diffusion of silver atoms on the surface of the powder, achieve connection, and thus greatly improve the conductivity of the silver-coated copper electrode. In addition, the onium compound can also reduce the electron transition barrier between the powder and the TCO substrate, thereby reducing the contact resistance between the electrode and the TCO substrate, thereby improving the photoelectric conversion efficiency of the battery. The paste can have a conductive property similar to that of pure silver paste (containing more than 92wt% silver) while reducing costs, thereby meeting the needs of cost reduction and efficiency improvement of heterojunction batteries.

[0051] In some embodiments of the present application, based on the total mass of the conductive paste, the mass proportion of the sintering agent is 0.05%-0.2%. For example, it can be 0.05%, 0.07%, 0.1%, 0.13%, 0.15%, 0.18%, 0.2%, etc., or it can be a range composed of any of the above numerical values. Therefore, by making the mass proportion of the sintering agent within the above range, the conductive performance of the silver-clad copper electrode can be improved, and the contact resistance between the electrode and the TCO substrate can be reduced. In addition, it is possible to avoid side effects such as poor adhesion caused by excessive sintering agent content and the slurry becoming viscous and affecting printing, or the sintering agent content is too low to achieve a good sintering effect.

[0052] In some embodiments of the present application, based on the total mass of the conductive paste, the mass proportion of the conductive powder is 88%-95%. For example, it can be 88%, 89%, 90%, 91%, 92%, 93%, 94%, 95%, etc., or it can be a range composed of any of the above numerical values. Thus, by making the mass proportion of the conductive powder within the above range, the slurry can have better conductivity and meet the requirements of the battery for electrode performance. In addition, ensure that the content of conductive powder is not too low, so as to avoid the increase of volume resistivity caused by poor contact between powders. At the same time, prevent the conductive powder content from being too high, resulting in the powder being unable to be evenly dispersed in the slurry, increasing the viscosity of the slurry, affecting its fluidity, and thus affecting the uniformity and precision of printing.

[0053] In some embodiments of the present application, based on the total mass of the conductive paste, the mass proportion of the thermosetting component is 1%-10%. For example, it can be 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, etc., or it can be a range composed of any of the above numerical values. Therefore, by making the mass proportion of the thermosetting component within the above range, the conductive paste can have better anti-corrosion properties and better adhesion, so that the conductive paste forms a uniform and stable film layer after curing, ensuring a firm bond between the electrode and the substrate. In addition, it is avoided that the conductive powder cannot be evenly dispersed due to too little content of the thermosetting component, and the adhesion of the cured product is poor; at the same time, it is avoided that the content of the thermosetting component is too large, which causes the conductive powder to have a smaller contact density or poor contact in the cured film layer, resulting in insufficient conductivity, resulting in an increase in volume resistivity.

[0054] In some embodiments of the present application, based on the total mass of the conductive paste, the mass proportion of the curing agent is 0.2%-1.5%. For example, it can be 0.2%, 0.5%, 0.7%, 1%, 1.2%, 1.5%, etc., or it can be a range composed of any of the above numerical values. Thus, by making the mass proportion of the curing agent within the above range, the thermosetting component can be prompted to undergo a curing reaction, thereby prompting the slurry to change from a liquid or semi-solid state to a solid state. In addition, it is necessary to avoid too low a curing agent content, which leads to incomplete curing or a long time to complete curing, and at the same time avoid too high a curing agent content, which leads to a slurry storage time that is too short and does not meet the storage requirements.

[0055] In some embodiments of the present application, the onium compound includes at least one of imidazolium, sulfonium, iodonium, and ammonium. Thus, the onium compound of the above type can produce material exchange with the surface of the silver powder, promote the mutual diffusion of silver atoms on the surface of the powder, achieve connection, and thus greatly improve the conductivity of the silver-coated copper electrode. At the same time, it can reduce the electron transition barrier between the powder and the TCO substrate, thereby reducing the contact resistance between the electrode and the TCO substrate.

[0056] It should be noted that the structural formula of imidazolium is The structural formula of sulfonium is R3S + , the structural formula of iodonium is R2I + The structural formula of ammonium is R4N + , wherein R is independently H or other substituents, and other substituents may be, for example, alkyl, alkenyl, aromatic or halogen. In addition, the number at the lower right corner of R in the structural formula of sulfonium, iodonium and ammonium represents the number of R, for example, "R3S + " means there are three R, wherein the three R can be independently selected from H, optionally substituted alkyl, optionally substituted alkenyl, optionally substituted aromatic or halogen, etc.

[0057] In some embodiments of the present application, R may be an optionally substituted C 1-10 Alkyl, optionally substituted C 2-10 an alkenyl group, an optionally substituted aromatic group or a halogen group, and the like.

[0058] In some embodiments of the present application, R may be an optionally substituted C 1-5 Alkyl, optionally substituted C 2-5 an alkenyl group, an optionally substituted aromatic group or a halogen group, and the like.

[0059] In some embodiments of the present application, the structure of the imidazolium may be: wait.

[0060] In some embodiments of the present application, the structure of the sulfonium may be: wait.

[0061] In some embodiments of the present application, the structure of the iodonium may be: wait.

[0062] In some embodiments of the present application, the structure of the ammonium onium may be: wait.

[0063] In some embodiments of the present application, the onium compound includes at least one of imidazolium, iodonium and ammonium.

[0064] In some embodiments of the present application, the conductive powder includes the silver powder and the silver-coated copper powder, and the mass ratio of the silver powder to the silver-coated copper powder is (20:80)-(30:70). For example, it can be 20:80, 22:78, 24:76, 25:75, 27:73, 30:70. Therefore, by making the mass ratio of silver powder to silver-coated copper powder within the above range, it is possible to effectively reduce the material cost while ensuring that the conductive paste has excellent conductive properties. In addition, the problem of insufficient density of the solidified material (such as electrodes, wiring, etc.) caused by too low silver powder content, thereby affecting the conductive performance, is avoided; and the silver powder content is prevented from being too high and unnecessarily increasing the cost.

[0065] In some embodiments of the present application, the specific shape of the conductive powder is not particularly limited, and any of the silver powder and the silver-coated copper powder may be spherical or quasi-spherical (granular), or may be flake or plate-shaped. There is no particular limitation on the silver powder (silver powder) and the silver-coated copper powder (silver-coated copper powder), and they may be known and commercially available.

[0066] In some embodiments of the present application, the specific physical properties of the conductive powder are not particularly limited, and the average particle size, specific surface area, tap density, etc. thereof can be within the known range.

[0067] For example, the average particle size D of the silver powder is 50 The range of the thickness may be 0.1 μm to 1 μm, for example, 0.1 μm, 0.2 μm, 0.5 μm, 0.8 μm, 1 μm, etc., or any range consisting of the above values.

[0068] For example, the BET specific surface area of ​​the silver powder is 0.2 m 2 / g-2.0m 2 / g. For example, it can be 0.2m 2 / g, 0.5m 2 / g, 0.8m 2 / g, 1m 2 / g, 1.5m2 / g, 2m 2 / g, etc., or may be within the range consisting of any of the above values.

[0069] For example, the tap density of the silver powder is 1.5 g / cm 3 -8g / cm 3 For example, it can be 1.5 g / cm 3 , 2g / cm 3 , 3g / cm 3 , 5g / cm 3 , 6g / cm 3 , 7g / cm 3 , 8g / cm 3 The above-mentioned arbitrary numerical ranges may also be used.

[0070] For example, the average particle size D of the silver-coated copper powder is 50 The diameter may be in the range of 2 μm to 10 μm, for example, 2 μm, 4 μm, 5 μm, 8 μm, 10 μm, etc., or in the range consisting of any of the above values.

[0071] For example, the BET specific surface area of ​​the silver-coated copper powder is 0.2 m 2 / g-2.0m 2 / g. For example, it can be 0.2m 2 / g, 0.5m 2 / g, 0.8m 2 / g, 1m 2 / g, 1.5m 2 / g, 2m 2 / g, etc., or may be within the range consisting of any of the above values.

[0072] For example, the tap density of the silver-coated copper powder is, for example, 1.5 g / cm 3 -8g / cm 3 For example, it can be 1.5g / cm 3 , 2g / cm 3 , 3g / cm 3 , 5g / cm 3 , 6g / cm 3 , 7g / cm 3 , 8g / cm 3 The above-mentioned arbitrary numerical ranges may also be used.

[0073] In some embodiments of the present application, there is no particular restriction on the amount of silver coated in the silver-coated copper powder. When the mass of the metal powder in the silver-coated state is taken as 100%, the amount of silver coated, for example, can be in the range of 5%-18%. For example, it can be 5%, 7%, 10%, 12%, 14%, 16%, 18%, etc., or can be a range consisting of any of the above values.

[0074] In some embodiments of the present application, the thermosetting component includes at least one of a polyolefin main chain epoxy resin, a bisphenol epoxy resin, and an alicyclic epoxy resin. Among them, the polyolefin main chain epoxy resin has excellent anti-corrosion performance. Using it as a thermosetting component can make the slurry have better anti-corrosion performance, reduce the effect of acetic acid on the cured product formed after the conductive slurry is cured, and thus extend the service life of the battery.

[0075] In some embodiments of the present application, the thermosetting component includes the epoxy resin of the polyolefin backbone, the bisphenol epoxy resin and the alicyclic epoxy resin, and the mass ratio of the epoxy resin of the polyolefin backbone, the bisphenol epoxy resin and the alicyclic epoxy resin is (20-60): (20-56): (12-40). For example, it can be 20:50:30, 40:40:20, 50:30:20, 60:20:20, 20:56:24, 30:30:40, 32:56:12, etc., or it can be a range composed of any of the above numerical values. By making the mass ratio of the epoxy resin of the polyolefin backbone, the bisphenol epoxy resin and the alicyclic epoxy resin within the above range, the conductive paste can have good anti-corrosion performance and good adhesion, and the conductive paste can be firmly adhered to the substrate.

[0076] In some embodiments of the present application, based on the total mass of the thermosetting component, the mass proportion of the epoxy resin of the polyolefin main chain is 20%-60%. For example, it can be 20%, 30%, 40%, 50%, 60%, etc., or it can be a range composed of any of the above numerical values. In this way, the conductive paste can have excellent anti-corrosion properties, while avoiding the poor reliability of the cured product (such as an electrode) formed after the conductive paste is cured due to the low content of epoxy resin in the polyolefin main chain, and the strong fluidity of the paste caused by the high content, which causes printing overflow, which is not conducive to the thinning of the grid lines.

[0077] In some embodiments of the present application, based on the total mass of the bisphenol epoxy resin and the alicyclic epoxy resin, the mass ratio of the bisphenol epoxy resin to the alicyclic epoxy resin is (50:50)-(70:30). For example, it can be 50:50, 55:45, 60:40, 65:35, 70:30, etc., or it can be a range composed of any of the above numerical values. Thus, the cured product formed after the conductive paste is cured can have good adhesion and can be firmly adhered to the surface of the substrate, avoiding the insufficient rigidity and low hardness of the cured product caused by too low content of bisphenol epoxy resin, and the greater brittleness of the cured product caused by too high content of bisphenol epoxy resin, and the easy cracking of the microstructure.

[0078] In some embodiments of the present application, the epoxy resin with a polyolefin main chain includes, but is not limited to, at least one of plant polyphenol epoxy resin, epoxidized polyolefin polyol, and epoxidized hydroxyl acrylic resin.

[0079] In some embodiments of the present application, the bisphenol epoxy resin includes but is not limited to at least one of bisphenol F epoxy resin, bisphenol S epoxy resin, and bisphenol A epoxy resin.

[0080] In some embodiments of the present application, the alicyclic epoxy resin includes but is not limited to at least one of 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexylcarboxylate, bis(7-oxabicyclo[4.1.0]3-heptylmethyl)adipate, tetrahydrophthalic acid diglycidyl ester, and hexahydrophthalic acid diglycidyl ester.

[0081] In some embodiments of the present application, the curing agent includes at least one of a thermal cationic curing agent and a blocked polyisocyanate curing agent, thereby promoting the curing reaction of the thermal curing component, thereby causing the slurry to transform from a liquid or semi-solid state to a solid state.

[0082] In some embodiments of the present application, the curing agent includes the thermal cationic curing agent and the blocked polyisocyanate curing agent, and the mass ratio of the thermal cationic curing agent to the blocked polyisocyanate curing agent is (0.5-1):1, for example, it can be 0.5:1, 0.6:1, 0.7:1, 0.8:1, 0.9:1, 1:1, etc., or it can be a range composed of any of the above values. Thus, by making the mass ratio of the thermal cationic curing agent to the blocked polyisocyanate curing agent within the above range, the thermal curing component can undergo a curing reaction faster, and the conductive paste can have a longer storage time. In addition, avoid too little content of the thermal cationic curing agent, which may result in incomplete curing of the thermal curing component or a long time to complete curing, and too high content, which may result in the storage time of the conductive paste being too short and not meeting the preservation requirements; avoid too low content of the blocked polyisocyanate curing agent, which may result in a decrease in the curing shrinkage rate of the thermal curing component, weakened aggregation effect on metal powder, and decreased conductivity, and too high content, which may result in too high a curing shrinkage rate of the thermal curing component, causing poor contact between the cured product and the substrate.

[0083] In some embodiments of the present application, the blocked polyisocyanate curing agent is a compound formed by blocking a polyisocyanate compound. According to the embodiments of the present application, there is no particular limitation on the blocking agent of the polyisocyanate compound, and imidazoles, phenols, oximes, etc. can be used appropriately.

[0084] In some embodiments of the present application, the polyisocyanate curing agent includes at least one of aromatic isocyanate and aliphatic polyisocyanate. According to an embodiment of the present application, the aromatic isocyanate includes but is not limited to at least one of toluene diisocyanate, diphenylmethane diisocyanate, polymethylene polyphenyl polyisocyanate, dimethyl diphenyl diisocyanate, xylylene diisocyanate, naphthalene diisocyanate, etc. According to an embodiment of the present application, the aliphatic polyisocyanate includes but is not limited to at least one of hexamethylene diisocyanate, isophorone diisocyanate, hydrogenated xylylene diisocyanate, dicyclohexylmethane diisocyanate, octamethylene diisocyanate, trimethyl hexamethylene diisocyanate, etc.

[0085] It should be noted that the "blocked polyisocyanate curing agent" described in the present application can be purchased or homemade, and the present application conducts relevant experiments by using the purchased blocked polyisocyanate curing agent.

[0086] In some embodiments of the present application, the thermal cationic curing agent includes at least one of a thermal cationic curing agent containing nitrogen atoms and a thermal cationic curing agent containing fluorine atoms. According to an embodiment of the present application, the thermal cationic curing agent includes but is not limited to at least one of boron trifluoride ethyl ether, boron trifluoride phenol, boron trifluoride piperidine, boron trifluoride acetate, boron trifluoride monomethylamine, boron trifluoride monoethylamine, boron trifluoride triethanolamine, and boron trifluoride monoethanolamine.

[0087] In some embodiments of the present application, there is no particular limitation on the solvent used in the present application, as long as the viscosity or fluidity of the conductive paste involved in the present application specification can be adjusted. The present application has no particular limitation on the viscosity of the conductive paste, and it can be adjusted within an appropriate range according to the method for forming the conductor pattern (such as screen printing, etc.). Similarly, the fluidity and other properties of the conductive paste can also be adjusted to an appropriate range according to various conditions.

[0088] In some embodiments of the present application, the present application does not particularly limit the specific types of solvents, for example, ether esters such as diethylene glycol butyl ether acetate and carbitol butyl ether acetate; ethers such as diethylene glycol diethyl ether and butyl carbitol (diethylene glycol monobutyl ether); alcohol ethers such as alcohol esters 12, tripropylene glycol monobutyl ether, tripropylene glycol methyl ether, tripropylene glycol methyl ether, and terpineol; dibasic acid esters (DBE), 2,2,4-trimethyl-1,3-pentanediol monoisobutyl ester, 2,2,4-trimethyl-1,3-pentanediol diisobutyl ester, etc. These solvents can be used alone or in appropriate combinations of two or more.

[0089] In some embodiments of the present application, the present application does not particularly limit the content of the solvent, and the solvent can be added to a degree that can adjust the viscosity or fluidity of the conductive paste to an appropriate range. It should be noted that in the embodiments of the present application, when the total amount of each component of the conductive paste is 100 parts by mass, relative to the total conductive paste, if the content of the solvent exceeds 10% by mass, the viscosity of the conductive paste is too low and the conductive paste has poor molding ability; if the content of the solvent is less than 2% by mass, the viscosity of the conductive paste is too high, and the conductive paste loses the shear fluidity under the conventional construction process, and is difficult to use.

[0090] Method for preparing conductive paste

[0091] The present application proposes a method for preparing the aforementioned conductive paste. According to an embodiment of the present application, the method comprises: mixing a conductive powder, a thermosetting component, a curing agent, a sintering agent and a solvent; grinding the mixed product to obtain the conductive paste; wherein the sintering agent comprises an onium compound, and the conductive powder comprises at least one of silver powder and silver-coated copper powder. Thus, by adopting the method of the present application, a cost-effective conductive paste can be prepared, which can not only reduce production costs, but also exhibit excellent conductive properties when used as an electrode material. In addition, the conductive paste can also effectively reduce the contact resistance between the electrode and the TCO substrate, thereby improving the photoelectric conversion efficiency of the battery. Those skilled in the art can understand that this method has all the characteristics and advantages of the conductive paste described above, and will not be elaborated on here.

[0092] The preparation method of the conductive paste involved in the present application is not particularly limited, and a method known in the field of conductive paste can be appropriately used. As a representative example, a method of mixing the above-mentioned components according to a predetermined mixing ratio (quality standard) and premixing using a known mixing device can be cited. Examples of the mixing device include a planetary mixer, a three-roll mill, and the like.

[0093] It should be noted that, in the conductive paste involved in the present application, in addition to the above-mentioned conductive powder, thermosetting component, curing agent, sintering agent and solvent, various other additives known in the art may be added to the conductive paste as needed. There is no particular limitation on the additives, and specifically, for example, coupling agents, thixotropic agents, dispersants, leveling agents, antioxidants, defoaming agents, etc. These additives may be added within the range that does not hinder the effects of the present application specification.

[0094] application

[0095] The present application proposes an electrode. According to an embodiment of the present application, the electrode is formed by curing the conductive paste obtained by the aforementioned conductive paste or the aforementioned method. Therefore, the electrode prepared by the conductive paste of the present application has good conductivity, and at the same time can reduce the contact resistance between the electrode and the TCO substrate, thereby improving the photoelectric conversion efficiency of the battery. Those skilled in the art can understand that the electrode has all the characteristics and advantages of the conductive paste described above, and will not be described in detail here.

[0096] The method of patterning the electrode prepared using the conductive paste of the present application is not particularly limited, and various known formation methods can be appropriately used. Typically, screen printing can be cited, and printing methods such as steel plate printing and laser transfer can also be appropriately used.

[0097] The present application proposes a battery. According to an embodiment of the present application, the battery includes a TCO substrate and the aforementioned electrode. Therefore, the battery prepared using the electrode of the present application has excellent photoelectric conversion efficiency. Those skilled in the art can understand that the battery has all the features and advantages of the conductive paste described above, and will not be described in detail here.

[0098] In some embodiments of the present application, the TCO substrate is selected from materials known in the art, and illustratively may include indium tin oxide (ITO), fluorine-doped tin oxide (FTO), and tungsten-doped tin oxide (IWO).

[0099] The scheme of the present application will be explained below in conjunction with the embodiments. It will be appreciated by those skilled in the art that the following embodiments are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If no specific technology or conditions are indicated in the embodiments, the technology or conditions described in the literature in this area or the product specification are carried out. The reagents used or the instruments that do not indicate the manufacturer are all conventional products that can be obtained commercially.

[0100] Example 1

[0101] 1. Preparation of blocked polyisocyanate curing agent solution

[0102] Blocked polyisocyanate (purchased blocked diphenylmethane diisocyanate) and diethylene glycol butyl ether acetate were heated and stirred at a ratio of 40% to dissolve them uniformly, thereby obtaining a blocked polyisocyanate curing agent solution.

[0103] 2. Preparation of thermosetting components

[0104] Epoxidized polyolefin polyol, bisphenol F epoxy resin, and diglycidyl tetrahydrophthalate were mixed in a ratio of 30:30:40, and stirred evenly to obtain a thermosetting component.

[0105] 3. Preparation of conductive paste:

[0106] By mass, 20 parts of conductive powder, i.e., spherical silver powder (D 50 =0.3μm, BET specific surface area =1.30m 2 / g, tap density = 5.4g / cm 3 ), 73 parts of spherical silver-coated copper powder (D 50 =4.0μm, BET specific surface area = 0.3m 2 / g, tap density = 4.8g / cm 3 ), 1 part of the blocked polyisocyanate curing agent solution prepared in step 1, 0.3 parts of boron trifluoride ethyl ether, 3 parts of the heat curing component prepared in step 2, and a sintering agent: sulfonium (chemical structure is (CH3)3S +) 0.1 parts, solvent: diethylene glycol butyl ether acetate 2.6 parts, mixed by a planetary stirring degassing machine, and ground by a three-roll grinder to obtain a conductive silver paste.

[0107] Example 2

[0108] Conductive silver paste was prepared according to the method described in Example 1, except that the amount of sulfonium was 0.05 parts.

[0109] Example 3

[0110] Conductive silver paste was prepared according to the method described in Example 1, except that the amount of sulfonium was 0.2 parts.

[0111] Example 4

[0112] Conductive silver paste was prepared according to the method described in Example 1, except that the amount of sulfonium was 0.01 parts.

[0113] Example 5

[0114] Conductive silver paste was prepared according to the method described in Example 1, except that the amount of sulfonium was 0.5 parts.

[0115] Example 6

[0116] Conductive silver paste was prepared according to the method described in Example 1, except that sulfonium was replaced by imidazolium (chemical formula: ).

[0117] Example 7

[0118] Conductive silver paste was prepared according to the method described in Example 1, except that sulfonium was replaced by iodonium (chemical formula: ).

[0119] Example 8

[0120] Conductive silver paste was prepared according to the method described in Example 1, except that sulfonium was replaced by ammonium (chemical formula: (CH3)4N + ).

[0121] Example 9

[0122] Conductive silver paste was prepared according to the method described in Example 1, except that the amount of epoxidized polyolefin polyol was 2 parts.

[0123] Example 10

[0124] Conductive silver paste was prepared according to the method described in Example 1, except that the amount of epoxidized polyolefin polyol was 6 parts.

[0125] Embodiment 11

[0126] Conductive silver paste was prepared according to the method described in Example 1, except that the amount of epoxidized polyolefin polyol was 1 part.

[0127] Example 12

[0128] Conductive silver paste was prepared according to the method described in Example 1, except that the amount of epoxidized polyolefin polyol was 8 parts.

[0129] Example 13

[0130] Conductive silver paste was prepared according to the method described in Example 1, except that the epoxidized polyolefin polyol was replaced by plant polyphenol epoxy resin.

[0131] Embodiment 14

[0132] A conductive silver paste was prepared according to the method described in Example 1, except that the epoxidized polyolefin polyol was replaced by an epoxidized hydroxy acrylic resin.

[0133] Comparative Example 1

[0134] Conductive silver paste was prepared according to the method described in Example 1, except that the sintering promoter sulfonium was not added in step 4.

[0135] Comparative Example 2

[0136] Conductive silver paste was prepared according to the method described in Example 1, except that no epoxy resin with a polyolefin main chain was added to the thermosetting component.

[0137] The differences between Examples 1-14 and Comparative Examples 1-2 are shown in Table 1.

[0138] Table 1

[0139]

[0140] Performance Testing

[0141] 1. The viscosity of the conductive paste is measured by a rotational viscometer at 25°C, No. 14 rotor, when the speed is 10 r / min and the reading time is 4 minutes.

[0142] 2. Preparation of test electrodes: Adjust the scraper pressure of the screen printer to 0.18 MPa, print the conductive paste on the transparent conductive film (indium tin oxide) / silicon substrate through a printing process according to the design pattern of the test electrode, dry the conductive paste at a temperature of 170°C, and continue to raise the temperature to 200°C to solidify the conductive paste to form a metal electrode to obtain the test electrode.

[0143] 3. Electrode volume resistivity The resistance at both ends of the gate line is tested using a four-probe ohmmeter. The gate line is a heterojunction battery formed by a TCO substrate printed with a conductive paste. The specific measurement process is: use a resistor to test the resistance between two points, and then use a 3D microscope to test the width, height and cross-sectional area of ​​the gate line, and calculate the volume resistivity result according to the following formula:

[0144] Volume resistivity = resistance / grid line length × cross-sectional area of ​​the gate line / 100 = line resistance × cross-sectional area of ​​the gate line / 100.

[0145] 4. The contact resistance is measured using the TLM (transmission line model) method.

[0146] 5. Acid resistance test: Soak the electrode in 80% acetic acid and observe whether the solution turns blue within 30 minutes.

[0147] The slurries and corresponding electrodes obtained in the above-mentioned Examples 1-14 and Comparative Examples 1-2 were tested as follows, and the test results are shown in Table 2. The results show that the sintering agent in the range of 0.05wt%-0.2wt% can not only improve the conductivity, but also does not affect other properties of the slurry; the amount of anti-corrosion polyolefin epoxy resin is preferably between 20%-60%. Too little slurry will not have an anti-corrosion effect, and too much will cause serious overflow of the slurry during fine line printing. Therefore, the present application provides a slurry that has a low silver content and higher conductivity, while taking into account the reliability of the silver-coated copper paste.

[0148] Table 2

[0149]

[0150] Although the embodiments of the present application have been shown and described above, it can be understood that the above embodiments are exemplary and cannot be understood as limitations on the present application. Ordinary technicians in this field can change, modify, replace and modify the above embodiments within the scope of the present application.

Claims

1. A conductive paste, characterized in that: include: Conductive powder, thermosetting component, curing agent, sintering agent and solvent, Wherein, the sintering promoter includes an onium compound, and the conductive powder includes at least one of silver powder and silver-coated copper powder.

2. The conductive paste according to claim 1, characterized in that: Based on the total mass of the conductive paste, the mass proportion of the sintering promoter is 0.05%-0.2%; And / or, based on the total mass of the conductive paste, the mass proportion of the conductive powder is 88%-95%; And / or, based on the total mass of the conductive paste, the mass proportion of the thermosetting component is 1%-10%; And / or, based on the total mass of the conductive paste, the mass proportion of the curing agent is 0.2%-1.5%.

3. The conductive paste according to claim 2, characterized in that: The onium compound includes at least one of imidazolium, sulfonium, iodonium, and ammonium.

4. The conductive paste according to claim 2, characterized in that: The thermosetting component includes at least one of a polyolefin main chain epoxy resin, a bisphenol epoxy resin, and an alicyclic epoxy resin; And / or, the curing agent includes at least one of a thermal cationic curing agent and a blocked polyisocyanate curing agent.

5. The conductive paste according to claim 4, characterized in that: The conductive powder includes the silver powder and the silver-coated copper powder, and the mass ratio of the silver powder to the silver-coated copper powder is (20:80)-(30:70); And / or, the thermosetting component comprises the epoxy resin with a polyolefin main chain, the bisphenol epoxy resin and the alicyclic epoxy resin, and the mass ratio of the epoxy resin with a polyolefin main chain, the bisphenol epoxy resin and the alicyclic epoxy resin is (20-60):(56-20):(40-12); And / or, the curing agent comprises the thermal cationic curing agent and the blocked polyisocyanate curing agent, and the mass ratio of the thermal cationic curing agent to the blocked polyisocyanate curing agent is (0.5-1):1; And / or, the blocked polyisocyanate curing agent is a compound formed by blocking a polyisocyanate compound.

6. The conductive paste according to claim 5, characterized in that: The epoxy resin of the polyolefin main chain includes at least one of plant polyphenol epoxy resin, epoxidized polyolefin polyol, and epoxidized hydroxyl acrylic resin; And / or, the bisphenol epoxy resin includes at least one of bisphenol F epoxy resin, bisphenol S epoxy resin, and bisphenol A epoxy resin; And / or, the alicyclic epoxy resin includes at least one of 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexylcarboxylate, bis(7-oxabicyclo[4.1.0]3-heptylmethyl)adipate, tetrahydrophthalic acid diglycidyl ester, and hexahydrophthalic acid diglycidyl ester; And / or, the thermal cationic curing agent includes at least one of a thermal cationic curing agent containing nitrogen atoms and a thermal cationic curing agent containing fluorine atoms; optionally, the thermal cationic curing agent includes at least one of boron trifluoride ethyl ether, boron trifluoride phenol, boron trifluoride piperidine, boron trifluoride acetate, boron trifluoride monomethylamine, boron trifluoride monoethylamine, boron trifluoride triethanolamine, and boron trifluoride monoethanolamine; And / or, the polyisocyanate curing agent includes at least one of aromatic isocyanate and aliphatic polyisocyanate; optionally, the aromatic isocyanate includes at least one of toluene diisocyanate, diphenylmethane diisocyanate, polymethylene polyphenyl polyisocyanate, dimethyl diphenyl diisocyanate, xylylene diisocyanate, and naphthalene diisocyanate; optionally, the aliphatic polyisocyanate includes at least one of hexamethylene diisocyanate, isophorone diisocyanate, hydrogenated xylylene diisocyanate, dicyclohexylmethane diisocyanate, octamethylene diisocyanate, and trimethylhexamethylene diisocyanate.

7. A method for preparing the conductive paste according to any one of claims 1 to 6, characterized in that: include: The conductive powder, the thermosetting component, the curing agent, the sintering agent and the solvent are mixed; Grinding the mixed product to obtain the conductive paste; Wherein, the sintering promoter includes an onium compound, and the conductive powder includes at least one of silver powder and silver-coated copper powder.

8. An electrode, characterized in that: The conductive paste is formed by curing the conductive paste prepared by the conductive paste described in any one of claims 1 to 6 or the method described in claim 7.

9. A battery, characterized in that: The invention comprises a TCO substrate and the electrode according to claim 8.

10. The battery according to claim 9, characterized in that The TCO substrate includes at least one of indium tin oxide, fluorine-doped tin oxide, and tungsten-doped tin oxide.